Studying the clinical encounter with the Adaptive Leadership framework - Bailey Jr DE; Docherty SL; Adams JA; Carthron DL; Corazzini K; Day JR; Neglia E; Thygeson M; Anderson RA (Dove Medical Press, 2012)
Donald E Bailey Jr,1,2 Sharron L Docherty,1 Judith A Adams,1 Dana L Carthron,3 Kirsten Corazzini,1,2 Jennifer R Day,1 Elizabeth Neglia,1 Marcus Thygeson,4 Ruth A Anderson1,21School of Nursing, Duke University, 2Center for the Study of Aging and Human Development, Duke University, Durham, NC, 3School of Health Science, Division of Nursing, Winston Salem State University, Winston Salem, NC, 4Medical Services, Blue Shield of California, San Francisco, CA, USAAbstract: In this paper we discuss the concept of leadership as a personal capability, not contingent on one's position in a hierarchy. This type of leadership allows us to reframe both the care-giving and organizational roles of nurses and other front-line clinical staff. Little research has been done to explore what leadership means at the point of care, particularly in reference to the relationship between health care practitioners and patients and their family caregivers. The Adaptive Leadership framework, based on complexity science theory, provides a useful lens to explore practitioners' leadership behaviors at the point of care. This framework proposes that there are two broad categories of challenges that patients face: technical and adaptive. Whereas technical challenges are addressed with technical solutions that are delivered by practitioners, adaptive challenges require the patient (or family member) to adjust to a new situation and to do the work of adapting, learning, and behavior change. Adaptive leadership is the work that practitioners do to mobilize and support patients to do the adaptive work. The purpose of this paper is to describe this framework and demonstrate its application to nursing research. We demonstrate the framework's utility with five exemplars of nursing research problems that range from the individual to the system levels. The framework has the potential to guide researchers to ask new questions and to gain new insights into how practitioners interact with patients at the point of care to increase the patient's ability to tackle challenging problems and improve their own health care outcomes. It is a potentially powerful framework for developing and testing a new generation of interventions to address complex issues by harnessing and learning about the adaptive capabilities of patients within their life contexts.Keywords: nursing, patient care, providers, health care practitioners, patient centered care, nursing providers, complex adaptive systems